Passive immunization prevents induction of Lyme arthritis in LSH hamsters. - Schmitz, J L (Infect Immun, 1990)
We determined that sera obtained from hamsters infected with Borrelia burgdorferi could prevent the induction of Lyme arthritis. When irradiated hamsters were administered immune serum and subsequently challenged with B. burgdorferi, no evidence of infection was detected. Recipients failed to develop swelling of the hind paws, and no histopathologic changes were detected. In addition, B. burgdorferi was not recovered from tissues of hamsters that were passively immunized. By contrast, irradiated hamsters that were administered normal hamster serum or saline and infected with the Lyme spirochete developed arthritis. Extensive histopathologic changes occurred in the hind paws and knee joints, and spirochetes were recovered from most of the tissues examined. These results show that immune serum can confer complete protection on recipient hamsters to challenge with B. burgdorferi. IMAGES: